2010
DOI: 10.5897/jmpr09.565
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and medicinal importance of mushrooms

Abstract: Mushrooms had long been used for medicinal and food purposes since decades. It is now increasingly recognized that correct diet, controls and modulates many functions of human body and consequently participates in the maintenance of state of good health, necessary to reduce the risk of many diseases. Modern pharmacological research confirms large parts of traditional knowledge regarding the medicinal effects of mushrooms due to their antifungal, antibacterial, antioxidant and antiviral properties, besides bein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
77
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 242 publications
(82 citation statements)
references
References 70 publications
2
77
2
1
Order By: Relevance
“…Mushrooms are edible fungi whose food value lies between meat and vegetables (Bano, ). Besides nutritional, mushrooms have medicinal importance (Bilal et al ., ) and have been used in health care for treating skin diseases (Breene, ; Gunde‐Cimmerman, ), tumours (Ikekawa et al ., ), epilepsy, wounds, heart ailments, rheumatoid arthritis, and have been used as vermicides (Bahl, ). The phenolic content and antioxidant activity in eight edible mushrooms, including Boletus edulis, have already been studied (Vidović et al ., ; Palacios et al ., ) and their results showed that the homogentisic acid was the phenolic acid significantly present in all mushrooms, while in sixteen different Portuguese wild mushroom species (Barros et al ., ), the p ‐hydroxybenzoic acid was determined to be the main acid.…”
Section: Introductionmentioning
confidence: 99%
“…Mushrooms are edible fungi whose food value lies between meat and vegetables (Bano, ). Besides nutritional, mushrooms have medicinal importance (Bilal et al ., ) and have been used in health care for treating skin diseases (Breene, ; Gunde‐Cimmerman, ), tumours (Ikekawa et al ., ), epilepsy, wounds, heart ailments, rheumatoid arthritis, and have been used as vermicides (Bahl, ). The phenolic content and antioxidant activity in eight edible mushrooms, including Boletus edulis, have already been studied (Vidović et al ., ; Palacios et al ., ) and their results showed that the homogentisic acid was the phenolic acid significantly present in all mushrooms, while in sixteen different Portuguese wild mushroom species (Barros et al ., ), the p ‐hydroxybenzoic acid was determined to be the main acid.…”
Section: Introductionmentioning
confidence: 99%
“…Bahl (1983) [17] reported that mushrooms cure epilepsy, wounds, skin diseases, heart aliments, rheu-matoid arthritis, cholera besides intermittent fevers, diaphoretic, diarrhoea, dysentery, cold, anaesthesia, liver and gall bladder diseases, and are used as vermicides. Nowadays the data show many other benefities of mushrooms in medicine, and without side effects [18].…”
Section: Introductionmentioning
confidence: 99%
“…Mushrooms had long been used for medicinal and food purposes since decades (Bilal et al 2010). Dried fungi and concentrated extracts are also used as medicines and dietary supplements (de Román et al 2006).…”
Section: Introductionmentioning
confidence: 99%